Tribological Behaviors of Porous 3D Graphene Lubricant Reinforced Monomer Casting Polyamide 6 Composite. Issue 5 (20th May 2020) - Wang, Liping; Pan, Bingli; Gao, Jiayu; Huang, Saisai; Xie, Mengxin; Li, Chunyan; Luo, Denglin; Liu, Jichun; Wang, Honggang
Abstract : A porous 3D graphene lubricant was designed with the merits of reducing the content of graphene dramatically and increasing the friction reduction and anti‐wear performances. This research as described in the article, number 1901170, by Bingli Pan and co‐workers, opens a new insight for designing 3D graphene composite in severe tribological conditions.